Penambahan Leksikal dalam Transformasi Penerjemahan Kitab Ta'limu Al Muta'allimi - Nafisah, Hana; Cholsy, Hayatul (Fakultas Teknik Universitas Negeri Makassar, 2025)
One of the main challenges in translating classical Arabic texts into Indonesian lies ini lexical addition, which may affect meaning and interpretation. This study aims to identify lexical addition in the translation of Ta’limu al Muta’allimi from Arabic to Indonesian.Using a qualitative descriptive method with translational equivalence approach, the data consist of word, phrases, and clauses from the source text and its Indonesian translation. The analysis reveals five main function of lexical additions: 1) providing supplementary information, 2) repeating key points, 3) emphasizing meaning, 4) conveying titles or honorifics, and 5) enchacing politeness markers. These findings indicate that lexical additions function not onlu as a linguistic strategy but also as a communicative and contextual means of transmitting educational and religious values. Thus, the translation of Ta’limu al Muta’allimi demonstrates both informative and normative dimensions